Examining U.S. school shootings as state crimes of omission - Finley, Laura L. (Contemporary justice review, 2023)
The argument presented in this paper is that the failure of the United States federal government to enact adequate gun control laws that would help prevent school shootings is a state crime by omission. Drawing on international law, as critical criminologists have recommended since the 1970s, the paper shows that the federal government is failing to act when it has a duty to protect schoolchildren. The paper concludes with recommendations for federal gun control.